Mercenaries or Peacekeepers? Comparing Executive Outcomes and ECOMOG in Sierra Leone - Adamo, Antonino (Africana Studia, 2021)
The paper compares two foreign interventions in Sierra Leone; the 1995 involvement of Executive Outcomes (EO), a South African private military company (PMC), against the Revolutionary United Front (RUF); and the intervention by the Economic Community of West African States Monitoring Group (ECOMOG, 1997-2000). A context analysis is performed, along with a focus on PMCs and African regional and sub-regional security systems, before an assessment of both interventions is provided. The paper highlights the failures experienced by both EO and ECOMOG: on the one hand, it reveals that EO intervention can be hardly considered as effective, due to its controversial legitimacy, accountability, etc., but on the other it points out at the technical, financial and political constraints as the main deficiencies of ECOMOG. Finally, the paper briefly introduces the most relevant achievements and developments experienced by ECOWAS/ECOMOG in terms of sub-regional peacekeeping in West Africa. Keywords: Sierra Leone, Executive Outcomes, ECOMOG, Mercenaries.